LIGHTCURVE ANALYSIS OF NEA 2009 FG19 - Warner, Brian D. (Minor Planet Bull, 2015)
CCD photometric observations of the near-Earth asteroid 2009 FG19 were made in 2014 September and October to supplement radar observations made at the same time. Analysis of the CCD data from September only found several possible periods, all commensurate with an Earth day. The most likely period was 8.00 ± 0.02 h with an amplitude of 0.80 ± 0.05 mag with an alternate solution of 9.61 ± 0.02 h being possible. The addition of data from October, even though the lightcurve had evolved noticeably, removed the 9.6 hour alias and confirmed the 8-hour solution. There were no obvious signs of non-principle axis rotation (NAPR; tumbling) but that cannot be formally excluded.